Zeolite 4A as a jammer of bacterial communication in chromobacterium violaceum and pseudomonas aeruginosa - TINAZ, GÜLGÜN (My University, 2022)
Aim: To investigate the hypothesis that zeolites interfere with quorum-sensing (QS) systems of Chromobacterium violaceum and Pseudomonas aeruginosa by adsorbing N-acyl homoserine lactone (AHL) signal molecules. Methods: QS inhibition by zeolite 4A was investigated using an AHL-based bioreporter assay. The adsorption of the AHLs was evaluated by performing inductively coupled plasma-optical emission spectroscopy and confirmed by Monte Carlo and molecular dynamic simulations. Results: Zeolite 4A reduced the violacein production in C. violaceum by over 90% and the biofilm formation, elastase and pyocyanin production in P. aeruginosa by 87, 68 and 98%, respectively. Conclusion: Zeolite 4A disrupts the QS systems of C. violaceum and P. aeruginosa by means of adsorbing 3-oxo-C6-AHL and 3-oxo-C12-AHL signaling molecules and can be developed as a novel QS jammer to combat P. aeruginosa-related infections.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Mikrobiyoloji; Yaşam Bilimleri (LIFE); MICROBIOLOGY; Life Sciences (LIFE); biofilms; modeling; Pseudomonas aeruginosa; quorum sensing; QUORUM SENSING INHIBITORS; BIOFILM FORMATION; ESSENTIAL OILS; GENES; DERIVATIVES; ADSORPTION; EXPRESSION; VIRULENCE; ENZYME; STEEL